Optimasi Pendistribusian Air dengan Metode North West Corner dan Metode Modified Distribution di PDAM Wae Manurung Kabupaten Bone - Syam, Rahmat; Ihsan, Hisyam; Muktamar, Muhammad Irham (Jurusan Matematika FMIPA UNM, 2021)
This study discusses the Optimization using types of transportation model that application North West Corner method (NWC) and Modified Distribution Method (MODI) on the stock of water in PDAM Wae Manurung Bone Regency. The water distribution data is formulated with a transportation model, so that in order to obtain the model is generated a balance model with addition dummy variable and export table water distribution, obtained a feasible initial solution by calculation using North West Corner method (NWC). Based on a feasible initial solution obtained the optimum solution using the Modified Distribution Method (MODI). The results of this study indicate that with the application of the Transportation Model there was a optimization occurs in water distribution costs in Bone Regency in June 2019 of 52.22% compared to the calculation results by PDAM Wae Manurung Bone Regency.